GO TO SCHOOL WITH TRANS KOETARADJA? BARRIES TO USING PUBLIC BUSSES AMONG STUDENTS - Najmi, Muazziss; Kamarullah, Kamarullah; Afif, Naufal; Rosyady, Phisca Aditya (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Traveling to school can contribute significantly to the physical activity of school students. However, in Indonesia, as in other countries, many school students are driven by their parents when they want to gain access to education at school. In this study, researchers highlight the obstacles to using the Bus Trans Koetaradja (BTK) in Banda Aceh, Indonesia, a city with chaotic parking and traffic jams, especially during working and school hours. The data were obtained and categorized based on the barriers through forum group discussions involving 86 junior and senior high school students. The findings show that distance to school, parental involvement, the influence of building structures, ignorance of information, convenience, and social perceptions are significant barriers to using BTK to or from school. These barriers can be a reference for the further development of BTK services for the wider community, especially among students. Not only does it applicable in Aceh Province, but other regions can also consider the improvement